Air-side Heat Transfer and Pressure Drop Characteristics of Louver-finned Aluminum Heat Exchangers at Different Inclination Angles - Nae-Hyun KIM; Do-Young KIM; Yong-Min CHOI; Ho-Won BYUN (Journal of Thermal Science and Technology, 2009)
The effect of inclination angle on the heat transfer and pressure drop characteristics of brazed aluminum heat exchangers having louvered fins is experimentally investigated. Three samples having different fin pitches (1.25, 1,5 and 2.0 mm) were tested. Results show that heat transfer coefficients are not affected by the inclination angle. Friction factors, however, increase as the inclination angle increases, with negligible difference between the forward and the backward inclination. Both the heat transfer coefficient and the friction factor are the smallest at Fp = 1.5 mm, followed by 2.0 mm and 1.25 mm. Possible explanation is provided considering the louver layout. Comparison of the present data with existing correlations is also made.